Cartografia da produção acadêmica sobre ensino religioso no Estado de Goiás(1997-2021): o Estado do conhecimento em teses e dissertações - (:unkn) unknown (Universidade Estadual de Goiás, 2022)
This work is the result of research carried out in the Interdisciplinary Graduate Program in Education, Language and Technology (PPG-IELT), at the State University of Goiás (UEG), entitled Cartography of academic production on Religious Education in the State of Goiás (1997 -2021): The State of Knowledge in Theses and Dissertations. Its object is Religious Education and the general objective is centered on revealing the place of the discipline Religious Education in academic productions carried out in the State of Goiás between the years 1997 and 2021. The methodological path to achieve this objective approaches the Phenomenological Method, with a qualitative, exploratory approach, based on the literature review procedure. The theoretical corpus is based on Bhabha (2019), Hall (2020), Koselleck (2014), Reis (2012), Castro (2009), Rodrigues, Junqueira and Martins Filho (2015), Silva (2000), among others. Academic productions on Religious Education in the State of Goiás are analyzed at Master's and Doctorate levels, the analyzes were organized based on the Social Cartography proposed by Gilles Deleuze and Félix Guattari (2019). As a result, it is observed in academic productions that: Religious Education has gone through conflicting paths in its history and has been constantly reformulated through the methodological prisms adopted by researchers who have proposed to elevate Religious Education to the position of main phenomenon in their investigations. With the enactment of Law No. 9,394, of December 20, 1996, the Law of Guidelines and Bases for National Education (LDB), the subject Religious Education began to have legislative support in relation to religious freedom and pedagogical practices aimed at cultural diversity and religious. It was possible to affirm, in this way, that its teaching-learning possibilities behave as a device for interaction and social intervention, with the objective of forming subjects with a focus on valuing diversity and respecting differences. It should be noted that the pedagogical practice of Religious Education followed paths that are aimed at the encounter between Society and School, offering subjects a fertile field for dialogue about their perceptions of the world and their performance as citizens. The discipline of Religious Education, therefore, is an anthropological phenomenon, present since the beginning of Brazilian society and, because of this, it contributes to the construction of the cultural identities of the subjects.
Cartography of academic production on religious education in the state of Goiás(1997- 2021): the State of knowledge in these and dissertations
Keywords: Ensino religioso; Ensino religioso - Cartografia social; Educação e religião na escola; Religious teaching; Religious teaching - Social cartography; Education and religion at school; CIENCIAS HUMANAS::EDUCACAO; CIENCIAS HUMANAS::TEOLOGIA